Familial Association of Granulocyte-Macrophage Colony-Stimulating Factor Autoantibodies in Inflammatory Bowel Disease. Issue 5 (May 2018) - Wright, Sandra S.; Trauernicht, Anna; Bonkowski, Erin; McCall, Courtney A.; Maier, Elizabeth A.; Bezold, Ramona; Lake, Kathleen; Chalk, Claudia; Trapnell, Bruce C.; Kim, Mi-Ok; Kugathasan, Subra; Denson, Lee A.
ABSTRACT: Objectives: Elevated granulocyte-macrophage colony-stimulating factor auto-antibodies (GM-CSF Ab) are associated with increased intestinal permeability and stricturing behavior in Crohn disease (CD). We tested for familial association of serum GM-CSF Ab level in CD and ulcerative colitis (UC) families. Methods: Serum GM-CSF Ab concentration was determined in 230 pediatric CD probands and 404 of their unaffected parents and siblings, and 45 UC probands and 71 of their unaffected parents and siblings. A linear mixed effects model was used to test for familial association. The intra-class correlation coefficient (ICC) was used to determine the degree of association of the serum GM-CSF Ab level within families in comparison with the degree of association among families. Results: The median (IQR) serum GM-CSF Ab concentration was higher in CD probands than in UC probands (1.5 [0.5, 5.4] μg/mL vs 0.7 [0.3, 1.6] μg/mL, P  = 0.0002). The frequency of elevated serum GM-CSF Ab concentration ≥1.6 μg/mL was increased in unaffected siblings of CD probands with elevated GM-CSF Ab, compared with unaffected siblings of CD probands without elevated GM-CSF Ab (33% vs 13%, respectively, P  = 0.04). A similar result was observed within UC families. In families of CD patients, the mean (95th CI) ICC was equal to 0.153 (0.036, 0.275), P  = 0.001, whereas in families of UC patients, the mean (95th CI) ICC was equal to 0.27 (0.24, 0.31), P  = 0.047. Conclusions: These data confirmed familial association of serum GM-CSF Ab levels. This could be accounted for by either genetic or environmental factors shared within the family. Abstract : Supplemental Digital Content is available in the text